2018
DOI: 10.1080/20477724.2018.1541160
|View full text |Cite
|
Sign up to set email alerts
|

Exploring insecticide resistance mechanisms in three major malaria vectors from Bangui in Central African Republic

Abstract: Malaria remains the main cause of mortality and morbidity in the Central African Republic. However, the main malaria vectors remain poorly characterised, preventing the design of suitable control strategies. Here, we characterised the patterns and mechanisms of insecticide resistance in three important vectors from Bangui. Mosquitoes were collected indoors, using electrical aspirators in July 2016 in two neighborhoods at Bangui. WHO bioassays performed, using F 2 An. gambiae sensu lato (s.l.), revealed a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
3
14
0
Order By: Relevance
“…The low genetic diversity observed in the partial fragment of the VGSC spanning exon 20, harboring the L1014F codon, suggests a restricted polymorphism of VGSC, highlighted by the very low number of haplotypes, as the 1014F allele nears fixation in this population. Our findings are consistent with previous studies reported in Central Africa [49, 60]. The fact that the predominant haplotype H3 matched with that found across Africa (H1-1014F) suggests a gene flow in An.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The low genetic diversity observed in the partial fragment of the VGSC spanning exon 20, harboring the L1014F codon, suggests a restricted polymorphism of VGSC, highlighted by the very low number of haplotypes, as the 1014F allele nears fixation in this population. Our findings are consistent with previous studies reported in Central Africa [49, 60]. The fact that the predominant haplotype H3 matched with that found across Africa (H1-1014F) suggests a gene flow in An.…”
Section: Discussionsupporting
confidence: 93%
“…coluzzii is consistent with previous results in countries bordering Cameroon, e.g. northern Nigeria where a 1014F kdr mutation frequency of 83% was reported [45], and in Central African Republic, with 52.3% for the 1014F resistant allele [49].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our knowledge, this is the first time the G119S Ace-1 mutation is clearly shown to be associated with carbamate resistance in Central African A. gambiae mosquito populations. Previous studies reporting the resistance to carbamates in A. gambiae mosquito populations from Central African countries did not detect the presence of Ace-1 G119S mutation in this region or did not establish such association [32,53,54,55,56,57].…”
Section: Discussionmentioning
confidence: 90%
“…coluzzii (Ngoussou colony); (ii) DNA from fully susceptible An. gambiae s.s. female (Kisumu colony); (iii) DNA from a susceptible female (SS- ace-1 ) of Central African Republic Origin [32]; and a negative control (1 μl of ddH 2 O).…”
Section: Methodsmentioning
confidence: 99%